The Effect of STEAM-Robotics on Science Subjects on Students' Ability to Solve Problems - Rochmatul Khikmiyah; Rusijono Rusijono; Fajar Arianto (AL-ISHLAH: Jurnal Pendidikan, 2021)
The development of the industrial and social revolutions today demands an increase in the quality of human resources who appear as intelligent humans and are able to solve problems. This study aims to determine the effect of the STEAM-Robotics approach in science learning on students' ability to solve problems. So it is hoped that STEAM-Robotics can make students find innovative solutions to real problems and convey them well. This study used an experimental research design, pretest-posttest control group design with one type of treatment. Methods of data collection are done using observation and performance tests. This research was conducted on 81 grade VII students with two T-test analyses, namely the pretest and post-test results of the experimental and control groups. The results showed that the STEAM-Robotics approach in science subjects affected students' problem-solving ability.